The effect of task constraints on idea generation in creative word-formation group work for beginner-level German learners. (December 2021) - Lindenberg, Dennis
Abstract: This study investigated the emergence of ideas at a word-formation level in group tasks with and without a formal constraint condition (alliteration). Japanese beginner-level learners of German were asked to work in triads to invent and explain German compound nouns. Applying the methodological framework of conversation analysis, all interaction between students was transcribed and coded for instances of self- or other-directed idea proposals for completing the task in German or Japanese. The dialogical nature of creativity was further described by number and quality of language-related episodes (LREs) revolving around explanation proposals per idea. The formal constraint in the task design caused a change in the students' approach and shifted the initial focus from meaning to form. Consequently, more ideas occurred in the students' second language and compound nouns were built ad hoc, resulting in higher opacity. This in turn caused more incidents of collaborative explanation proposals. The study suggests that putting formal constraints on tasks for beginner-level language learners can guide students in using and noticing more unfamiliar vocabulary, which may lead to collaborative language play regarding semantic extensions and meta-linguistic features. Highlights: Language play enables beginner-level learners to do hypotheses testing and collaborative languaging about the TL in their L1. A formal constraint led to fewer proposed ideas, but ideas usually happened in the L2 and were followed by elaborate LREs. Opaque ideas allow more room for creative negotiation of meaning. Creativity is actively evaluated and enjoyed by learners.